Clopidogrel-Induced Neutropenia after Coronary Stenting: Is Cilostazol a Good Alternative? - Massimo Montalto; Italo Porto; Antonella Gallo; Claudia Camaioni; Roberta Della Bona; Antonio Grieco; Filippo Crea; Raffaele Landolfi (International Journal of Vascular Medicine)
Dual antiplatelet therapy with aspirin plus thienopyridines has become the standard treatment of patients undergoing coronary stenting. Clopidogrel has mostly replaced the use of ticlopidine due to its more favourable adverse event profile. However, also the use of clopidogrel is not without side effects. Clopidogrel major adverse events are represented by marrow suppression, manifesting with aplastic anaemia, thrombocytopenia and neutropenia. When clopidogrel toxicity occurs, there are few and unsubstantiated alternative treatments and thus, in these cases, medical decisions may be very difficult. We report a case of clopidogrel-induced bone marrow toxicity manifesting with severe neutropenia in a patient treated with multiple coronary stents and provide suggestions for an alternative treatment.